Gender representation in english language teaching materials: a descriptive case study (2022)
This research explores gender practices in English Language Teaching (ELT) settings, particularly in the Colombian context. While gender dynamics in education environments have been discussed internationally, there is a need for further exploration in Colombia to foster an inclusive society. This qualitative case study with a content analysis methodology observed and reflected on the practices and materials used by two experienced C1-level language teachers in an ELT classroom at a public university in Pereira, Risaralda. Data analysis involved transcribing and categorizing the information collected from the classes observed. It was found that gender practices and stereotypes were presented in the material, however teachers acknowledged these biases and promoted a space for reflection and a critical analysis of the material. On this way the teachers promoted an inclusive space for interaction that intended to diminish the impact of these biases on their classes.